Taking stock of "Organizational Learning": Looking back and moving forward. Issue 3 (July 2022) - Elkjaer, Bente
In what ways are organizational learning a relevant theoretical construct? The article taps into a debate on what is relevance to practitioners versus researchers' responsibility. The publications on organizational learning are on the rise, but the patterns have changed and points to a bifurcation within the field of organizational learning. On one hand, organizational learning is a means to further organizational performance, a fixed goal to be measured, which sometimes demands unlearning. On the other hand, there is a call for organizational learning to be encompassing contemporary societal challenges like widespread digitalization, sustainable production, and an inclusive labor market. This may appear as a cleavage between immediate relevance to practitioners and researchers' responsibilities for the development of relevant and critical knowledge. I propose to embrace a pragmatist theory of learning that can help address the unknown and include creative imagination directed toward developing an organizational learning field, which is also ready for the future.